Measles vaccination and antibody response in autism spectrum disorders. Issue 10 (5th February 2008) - Baird, G; Pickles, A; Simonoff, E; Charman, T; Sullivan, P; Chandler, S; Loucas, T; Meldrum, D; Afzal, M; Thomas, B; Jin, L; Brown, D
Abstract : Objective: To test the hypothesis that measles vaccination was involved in the pathogenesis of autism spectrum disorders (ASD) as evidenced by signs of a persistent measles infection or abnormally persistent immune response shown by circulating measles virus or raised antibody titres in children with ASD who had been vaccinated against measles, mumps and rubella (MMR) compared with controls. Design: Case–control study, community based. Methods: A community sample of vaccinated children aged 10–12 years in the UK with ASD (n = 98) and two control groups of similar age, one with special educational needs but no ASD (n = 52) and one typically developing group (n = 90), were tested for measles virus and antibody response to measles in the serum. Results: No difference was found between cases and controls for measles antibody response. There was no dose–response relationship between autism symptoms and antibody concentrations. Measles virus nucleic acid was amplified by reverse transcriptase-PCR in peripheral blood mononuclear cells from one patient with autism and two typically developing children. There was no evidence of a differential response to measles virus or the measles component of the MMR in children with ASD, with or without regression, and controls who had either one or two doses of MMR. Only one child from the control group had clinical symptoms of possible enterocolitis. Conclusion: No association between measles vaccination and ASD was shown.